Quail and Rain: What's the Relationship? - William M. Giuliano; R. Scott Lutz (National Quail Symposium Proceedings, 2017)
We used Christmas Bird Count reports in conjunction with precipitation data from 9 locations in Texas, to investigate relationships between rainfall and northern bobwhite (Colinus virginianus) and scaled quail (Callipepla squamata) abundance. Regional differences in northern bobwhite abundance could not be predicted by precipitation regimes, whereas scaled quail abundance was negatively correlated with fall and winter rainfall. Differences in rainfall patterns were not significantly correlated with year-to-year changes in northern bobwhite and scaled quail abundance.
Keywords: distribution; northern bobwhite; population fluctuations; regulating factors; scaled quail